2014
DOI: 10.5664/jcsm.3604
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Improvement with Continuous Positive Airway Pressure is Independent of Obstructive Sleep Apnea Severity

Abstract: OSA patients with uncontrolled hypertension are likely to gain the largest benefit from PAP in terms of a substantial reduction in BP, even after controlling for disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…The magnitude of the drop in BP is subject to various factors such as CPAP compliance [145, 146, 150, 151], duration of treatment with CPAP [145, 152] and its use during REM sleep [153], presence of EDS [146, 150], baseline BP [145, 147], and severity of OSAS with increased benefits seen in patients with baseline AHI > 30 [140, 146] and a high BMI [141, 154]. Patients who exhibited higher baseline BP, untreated hypertension, nocturnal hypertension/nondipper pattern, and resistant hypertension were found to benefit the most with CPAP therapy [141, 155157].…”
Section: Treatmentmentioning
confidence: 99%
“…The magnitude of the drop in BP is subject to various factors such as CPAP compliance [145, 146, 150, 151], duration of treatment with CPAP [145, 152] and its use during REM sleep [153], presence of EDS [146, 150], baseline BP [145, 147], and severity of OSAS with increased benefits seen in patients with baseline AHI > 30 [140, 146] and a high BMI [141, 154]. Patients who exhibited higher baseline BP, untreated hypertension, nocturnal hypertension/nondipper pattern, and resistant hypertension were found to benefit the most with CPAP therapy [141, 155157].…”
Section: Treatmentmentioning
confidence: 99%
“…32,38 Despite these limits, several meta-analyses demonstrated a concordant mild effect of CPAP on blood pressure, with a drop of approximately 2-3 mmHg, in particular during night time (Table 5). 32,[39][40][41][42][43][44][45] These studies showed that the biggest reduction in BP values is present in some subgroups of subjects: 38 i) uncontrolled and resistant hypertension; ii) OSA severe; iii) major symptoms (daytime sleepiness); iv) better compliance to CPAP (at least 5-6 h/night). …”
Section: Which Drugs Should Be Used?mentioning
confidence: 99%
“…In these investigators' models none of the severity of apnea, the Epworth Sleepiness Scale score, age, sex, body mass index, or CPAP adherence predicted the blood pressure response to treatment (89). These findings have two implications.…”
Section: Randomized Treatment Trialsmentioning
confidence: 81%
“…Finally, none of the meta-analyses considered the far greater hemodynamic benefit of abolishing cyclical oscillations in left ventricular and left atrial trans-mural pressures with CPAP (82, 85-87, 89, 90) Why, considering the adverse autonomic, humoral and cardiovascular effects of OSA is the impact of CPAP on the blood pressure of hypertensive patients so modest or even absent? The findings of a recent meta-analysis argue against the proposition that the response to therapy is a function of pre-treatment somnolence (89) whereas the hypothesis that a minimum threshold of adherence is required to detect benefit is biologically plausible (80). Both the severity of daytime somnolence before treatment is initiated (84) and the time of day that blood pressure is measured may be critical: one of the largest falls in average blood pressure reported, albeit in a heart failure cohort, was detected when patients were evaluated in hospital shortly after waking (60).…”
Section: Randomized Treatment Trialsmentioning
confidence: 87%